Estimation of regional gas and tissue volumes of the lung in supine man using computed tomography. Issue 8 (August 1986) - Denison, D M; Morgan, M D; Millar, A B
Abstract : This study was intended to discover how well computed tomography could recover the volume and weight of lung like foams in a body like shell, and then how well it could recover the volume and weight of the lungs in supine man. Model thoraces were made with various loaves of bread submerged in water. Computed tomography scans recovered the volume of the model lungs (true volume range 250-12, 500 ml) within +0.2 (SD 68) ml and their weights (true range 72-3125 g) within +30 (78) g. Scans also recovered successive injections of 50 ml of water, within +/- 5 ml. Scans in 12 healthy supine men recovered their vital capacities, total lung capacities (TLC), and predicted tissue volumes with comparable accuracy. At total lung capacity the mean tissue volume of single lungs was 431 (64) ml and at residual volume (RV) it was 427 (63) ml. Tissue volume was then used to match inspiratory and expiratory slices and calculate regional ventilation. Throughout the mid 90% of lung the RV/TLC ratio was fairly constant--mean 21% (5%). New methods of presenting such regional data graphically and automatically are also described.